Examining The Influence of Influencers and Social Media Marketing on Online Decision-Making: The Mediating Role of Fear of Missing Out (Fomo) Among Indonesian E-Commerce Users Aged 25–45 Years - Bagus Riyadistya; Susmawindardhani; Siti Mujanah; Estik Hari Pratiwi (International Journal of Economics (IJEC), 2026)
This study aims to examine the empirical and theoretical evidence concerning the role of influencer marketing and Social Media Marketing Activities (SMMA) in shaping online decision-making, with Fear of Missing Out (FOMO) serving as a mediating variable among Indonesian e-commerce users aged 25–45 years. This research employs a systematic literature review approach using narrative synthesis. Five national and international indexed journal articles, along with one consumer behavior textbook, were selected and analyzed based on the relevance of the variables, population characteristics, and their applicability to the Indonesian context. The findings consistently demonstrate that influencer marketing and SMMA exert a significant positive influence on Fear of Missing Out (FOMO), which subsequently mediates the relationship between these marketing activities and online purchasing decisions. Furthermore, two of the reviewed studies involving respondents within age ranges overlapping the target group (18–40 years and 25–44 years) indicate that FOMO is prevalent among individuals in the productive age category. Additional theoretical support is provided by the consumer behavior literature, which highlights the importance of social influence and consumer motivation in shaping purchasing behavior. From a managerial perspective, marketing strategies that leverage influencers and social media platforms to stimulate FOMO can effectively encourage purchasing decisions among consumers in the productive age segment. Future studies are recommended to focus specifically on e-commerce users aged 25–45 years to provide more comprehensive empirical evidence regarding this relationship